The Indus Investigators Mohenjodaro Mystery - Ilona Aronovsky (New Delhi Scholastic Inc, 2010)
On a school trip to the ancient ruins of Mohenjodaro two children, Mina and Yasin get caught in a time warp. Famous archaeologists who discovered the Indus Civilisation still haunt the place. Creatures of clay, stone and bronze come alive to guide them on a quest to see how life in this city was lived 4000 years ago. They meet deeper mysteries, what disasters caused the city to be deserted and forgotten in the mists of time. Mina and Yasin have fun, adventures and scares along the way. They become true investigators thanks to the awesome One-horn beast, the writing on the seals, Cart Man, some angry skeletons and a cast of human and animal figurines.
Keywords: Historical Fiction -- Historical Fiction